Climate Change: Evidence and Causes: Update 2020 (The National Academies Press, 2020)
Climate change is one of the defining issues of our time. It is now more certain than ever, based on many lines of evidence, that humans are changing Earth's climate. The Royal Society and the US National Academy of Sciences, with their similar missions to promote the use of science to benefit society and to inform critical policy debates, produced the original Climate Change: Evidence and Causes in 2014. It was written and reviewed by a UK-US team of leading climate scientists. This new edition, prepared by the same author team, has been updated with the most recent climate data and scientific analyses, all of which reinforce our understanding of human-caused climate change. Scientific information is a vital component for society to make informed decisions about how to reduce the magnitude of climate change and how to adapt to its impacts. This booklet serves as a key reference document for decision makers, policy makers, educators, and others seeking authoritative answers about the current state of climate-change science.

Leveraging Unmanned Systems for Coast Guard Missions - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
As unmanned systems (UxS) continue to develop and be used by other military services and federal agencies, the U.S. Coast Guard should proceed more aggressively and deliberately in taking advantage of UxS advancements, says a new congressionally mandated report from the National Academies of Sciences, Engineering, and Medicine.The Coast Guard should also produce a high-level strategy with critical goals and actionable steps toward fully utilizing UxS technology, according to TRB Special Report 335: Leveraging Unmanned Systems for Coast Guard Missions.UxS technologies include aerial, surface, and underwater vehicles with no human occupants; vehicles that may have a crew but with some level of remote control; and systems that are not vehicles.As one of the country2019s six military services, the Coast Guard also serves as a first responder, law enforcement agency, maritime regulator, and member of the intelligence community. Despite multiple initiatives to explore and assess the applicability of UxS to these areas, the Coast Guard lacks a formal means for identifying, investigating, and integrating systems. Meanwhile, UxS technological advancements continue to accelerate, driven by both commercial and military demands.

Guidance for Using the Interactive Tool for Understanding NEPA at General Aviation Airports - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Most general aviation (GA) airports are minimally staffed and rarely employ environmental specialists, and the National Environmental Policy Act (NEPA) can be overwhelming to work through for those not familiar with the requirements.The TRB Airport Cooperative Research Program's ACRP Research Report 211: Guidance for Using the Interactive Tool for Understanding NEPA at General Aviation Airports, and the accompanying interactive tool that was developed, will help airport staff from GA airports understand the NEPA process. The report provides an overview of NEPA, when it is applied, and the three levels of NEPA review. The tool will be helpful in better understanding the level of effort that may be required to comply with NEPA.An annotated bibliography, which was Appendix A to the Contractor2019s Final Report, is also available.

A Guide to Emergency Management at State Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
State transportation agencies will always fulfill a role in the emergency-management effort - for all incidents, from the routine traffic incident through major emergencies to catastrophic events. State agency plans and procedures are expected (indeed required if the agency seeks federal compensation) to be related to state and regional emergency structures and plans. This involves multi-agency, multi2010jurisdictional cooperation in emergency planning and operations.The TRB National Cooperative Highway Research Program's NCHRP Research Report 931: A Guide to Emergency Management at State Transportation Agencies is an update to a 2010 guide that provided an approach to all2010hazards emergency management and documented existing practices in emergency-response planning.Significant advances in emergency management, changing operational roles at state DOTs and other transportation organizations, along with federal guidance issued since 2010, have resulted in a need to reexamine requirements for state transportation agency emergency-management functions, roles, and responsibilities.The report is accompanied by NCHRP Web-Only Document 267:Developing a Guide to Emergency Management at State Transportation Agencies and a PowerPoint presentation that offers an overview and key findings, among other information.

Update of Security 101: A Physical Security and Cybersecurity Primer for Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Since 2009, when NCHRP's last Security 101 report was released, there have been significant advances in transportation security approaches, including new strategies, programs, and ways of doing business that have increased the security of transportation systems as well as ensured their resiliency.Hazards and threats to the system have also continued to evolve since 2009. While the incidence of large-scale terrorist attacks has remained small, transportation agencies are at increasingly greater risk from system-disrupting events due to natural causes, unintentional human intervention, and intentional criminal acts, such as active-shooter incidents. Cyber risks also are increasing and can impact not only data, but the control systems2014like tunnel-ventilation systems2014operated by transportation agencies.>The TRB National Cooperative Highway Research Program's NCHRP Research Report 930: Update of Security 101: A Physical Security and Cybersecurity Primer for Transportation Agencies provides valuable information about current and accepted practices associated with both physical and cyber security and its applicability to surface transportation.The report is accompanied by a PowerPoint for the project and NCHRP Web-Only Document 266: Developing a Physical and Cyber Security Primer for Transportation Agencies.

Evaluating the Suitability of Roadway Corridors for Use by Monarch Butterflies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Roadsides provide promising monarch habitat as they frequently contain nectar and host plants; however, they also present a range of risks, including pesticide spillover, vehicle collisions, contaminant runoff, and non-native vegetation.The TRB National Cooperative Highway Research Program's NCHRP Research Report 942: Evaluating the Suitability of Roadway Corridors for Use by Monarch Butterflies provides guidance for roadside managers to determine the potential of their roadway corridors as habitat for monarch butterflies.The report also includes several tools and decision-support mechanisms to optimize habitat potential in a manner that is compatible with the continued operation and maintenance of the roadside.

Airport Renewable Energy Projects Inventory and Case Examples - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Airports have implemented a variety of renewable energy technologies since 19992014with the largest growth occurring over the past decade2014in parallel with the evolution and maturation of renewable energy markets. Of the renewable energy options available to airports today, the prevailing technology is solar photovoltaic (PV), which accounts for 72% of all projects cataloged in the Renewable Energy Projects Inventory.The TRB Airport Cooperative Research Program's ACRP Synthesis 110: Airport Renewable Energy Projects Inventory and Case Examples draws on existing literature and data to present the state of practice for airport renewable energy. It presents the integration of renewable energy projects2014including solar PV, geothermal, bioenergy, solar thermal, and small wind projects2014into airport development and operations and the drivers behind those efforts.The Renewable Energy Projects Inventory in the report is also available online as a searchable database.

Deicing Planning Guidelines and Practices for Stormwater Management Systems, second edition - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The first edition of this report, in 2009, provided a comprehensive industry reference for the management of airport deicing runoff. The second edition has been wholly updated to reflect the latest industry practices.The TRB Airport Cooperative Research Program's ACRP Research Report 14: Deicing Planning Guidelines and Practices for Stormwater Management Systems, second edition, explores a wide array of practices designed to provide for the practical, cost-effective control of runoff from aircraft and airfield deicing and anti-icing operations.Additional resources with the report include a Set of Fact Sheets, a Decision Support Tool, a Decision Support Tool User Guide, and a Decision Support Tool Instructional Video.

Tax Increment Financing for Transit Projects - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Tax Increment Financing (TIF) is a public financing method that some local governments and transportation agencies may use to capture a portion of additional property (or sales) tax revenues that result when public investments cause property values (or total sales revenues) to increase. TIF is an increasingly important source of funds for transportation projects, and it has the potential to be a key part of project financing.The TRB Transit Cooperative Research Program'sTCRP Legal Research Digest 55: Tax Increment Financing for Transit Projects examines whether and under what circumstances TIF might be used to fund transit operations and maintenance, as well as the challenges that such arrangements might face.The digest includes case studies of Miami-Dade County, Chicago, Prince Georges County in Maryland, and more.

Airport Environmental Research Roadmap Narrative Report - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Airports must maintain a safe and efficient facility while considering environmental impacts. Though traditional environmental challenges such as noise and water quality remain, several new themes are emerging, including energy management, sustainability, resiliency, and wildlife management. Airports will need guidelines and practices to help them address these pressing issues, and the first step in the process is to identify knowledge gaps and research needs. The TRB Airport Cooperative Research Program2019s ACRP Web-Only Document 45: Airport Environmental Research Roadmap Narrative Report presents a five-year prioritized listing of research needs in the area of airport environmental management. The description of these needs can be used to develop research problem statements for funding consideration. Additional resources included with the report include a research-idea dataset and a Visual Research Roadmap.

Developing a Guide to Ensuring Access to the Publications and Data of Federally Funded Transportation Research - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 270: Developing a Guide to Ensuring Access to the Publications and Data of Federally Funded Transportation Research provides guidance for state departments of transportation (DOTs) to help them meet the requirements of the U.S. DOT Public Access Plan requiring preservation of the products of all federally funded transportation research.The document is released in parallel with NCHRP Research Report 936: Guide to Ensuring Access to the Publications and Data of Federally Funded Transportation Research.

Traffic Forecasting Accuracy Assessment Research - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Accurate traffic forecasts for highway planning and design help ensure that public dollars are spent wisely. Forecasts inform discussions about whether, when, how, and where to invest public resources to manage traffic flow, widen and remodel existing facilities, and where to locate, align, and how to size new ones.The TRB National Cooperative Highway Research Program's NCHRP Report 934: Traffic Forecasting Accuracy Assessment Research seeks to develop a process and methods by which to analyze and improve the accuracy, reliability, and utility of project-level traffic forecasts.The report also includes tools for engineers and planners who are involved in generating traffic forecasts, including: Quantile Regression Models, a Traffic Accuracy Assessment, a Forecast Archive Annotated Outline, a Deep Dive Annotated Outline, and Deep Dive Assessment Tables,

Guidebooks for Post-Award Contract Administration for Highway Projects Delivered Using Alternative Contracting Methods, Volume 3: Research Overview - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The use of alternative contracting methods (ACMs) has accelerated the delivery of highway design and construction projects. These changes came about through efforts of the Federal Highway Administration (FHWA) and state agencies over the last 30 years.The TRB National Cooperative Highway Research Program's NCHRP Research Report 939: Guidebooks for Post-Award Contract Administration for Highway Projects Delivered Using Alternative Contracting Methods, Volume 3: Research Overview provides the necessary methods and tools to help state agencies better administer Design2013Build (D-B) and construction manager2013general contractor (CM-GC) contracts on highway construction projects.This Research Report documents the rigorous process followed to produce these two Guidebooks.Vol. 1, on design-build delivery, and Vol. 2, on construction manager2013general contractor delivery, are also available.

Airports and Unmanned Aircraft Systems, Volume 2: Incorporating UAS into Airport Infrastructure— Planning Guidebook - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The introduction of unmanned aircraft systems (UAS) has presented a wide range of new safety, economic, operational, regulatory, community, environmental, and infrastructure challenges to airports and the National Airspace System. These risks are further complicated by the dynamic and shifting nature of UAS technologies.The Airport Cooperative Research Program's ACRP Research Report 212: Airports and Unmanned Aircraft Systems provides guidance for airports on UAS in the areas of managing UAS operations in the vicinity of an airport and engaging stakeholders (Volume 1), incorporating UAS into airport infrastructure and planning (Volume 2), and potential use of UAS by airport operators (Volume 3).Volume 2: Incorporating UAS into Airport Infrastructure2014 Planning Guidebook provides suggested planning, operational, and infrastructure guidance to safely integrate existing and anticipated UAS operations into an airport environment. This guidebook is particularly applicable to smaller airports (non-hub and general aviation) without capacity issues. The planning approach could help these airports prepare for and attract UAS operations for additional revenue in the near term.Volume 1: Managing and Engaging Stakeholders on UAS in the Vicinity of Airports provides guidance for airport operators and managers to interact with UAS operations in the vicinity of airports.Volume 3: Potential Use of UAS by Airport Operators provides airports with resources to appropriately integrate UAS missions as part of their standard operations.Supplemental resources to ACRP Research Report 212 are provided inACRP Web-Only Document 42: Toolkits and Resource Library for Airports and Unmanned Aircraft Systems.

Teaching K-12 Science and Engineering During a Crisis - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The COVID-19 pandemic is resulting in widespread and ongoing changes to how the K-12 education system functions, including disruptions to science teaching and learning environments. Students and teachers are all figuring out how to do schooling differently, and districts and states are working overtime to reimagine systems and processes. This is difficult and stressful work in the middle of the already stressful and sometimes traumatic backdrop of the global pandemic. In addition, students with disabilities, students of color, immigrants, English learners, and students from under-resourced communities have been disproportionately affected, both by the pandemic itself and by the resulting instructional shifts. Teaching K-12 Science and Engineering During a Crisis aims to describe what high quality science and engineering education can look like in a time of great uncertainty and to support practitioners as they work toward their goals. This book includes guidance for science and engineering practitioners - with an emphasis on the needs of district science supervisors, curriculum leads, and instructional coaches. Teaching K-12 Science and Engineering During a Crisis will help K-12 science and engineering teachers adapt learning experiences as needed to support students and their families dealing with ongoing changes to instructional and home environments and at the same time provide high quality in those experiences.

Guide to Ensuring Access to the Publications and Data of Federally Funded Transportation Research - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The U.S. Department of Transportation has essential requirements for researchers and research institutions requesting and receiving transportation-related federal research funds. The U.S. DOT strives to make it easier to publish and communicate scientific knowledge. It is a long-range vision which goes beyond the requirements of the U.S. DOT2019s Public Access Plan.The TRB National Cooperative Highway Research Program's NCHRP Research Report 936: Guide to Ensuring Access to the Publications and Data of Federally Funded Transportation Research is designed to help state DOTs, as well as other organizations that do transportation research, better understand and consider how they will comply with the U.S. DOT policy.The guide is accompanied by NCHRP Web-Only Document 270: Developing a Guide to Ensuring Access to the Publications and Data of Federally Funded Transportation Research.

Highway Hydraulic Engineering State of Practice - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The TRB National Cooperative Highway Research Program's NCHRP Synthesis 551: Highway Hydraulic Engineering State of Practice documents significant changes in highway hydraulic engineering practices implemented by state departments of transportation (DOTs) over the past decade.The synthesis focuses on eight subtopics of highway hydraulic engineering: roadway drainage; culvert aquatic organism passage; bridge scour computations and countermeasures; advanced hydraulic modeling; regulatory requirements; floodplain impacts and mitigation; coastal hydraulics; and alternative project delivery methods.

Surface from Under the Microscope: The Henrietta Lacks Series (The National Academies Press, 2020)

Solid-State Roadway Lighting Design Guide: Volume 1: Guidance - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The TRB National Cooperative Highway Research Program's NCHRP Research Report 940: Solid-State Roadway Lighting Design Guide: Volume 1: Guidance develops more comprehensive guidelines in American Association of State Highway Transportation Officials (AASHTO)-standard format for the application of roadway lighting related to the widespread adoption of SSL, and identifies gaps in knowledge where possible future research will enhance these guidelines. This report is not available from TRB nor the National Academies. The report will be published by AASHTO early in 2022.The guide that accompanying report is available for download at NCHRP Research Report 940: Solid-State Roadway Lighting Design Guide: Volume 2: Research Overview.